Liver resection by Ultrasonic Dissection and lntraoperative Ultrasonography. Issue 3 (1996) - Hanna, Sherif S.; Nam, Robert; Leonhardt, Charlene
Abstract : Ultrasonic dissetion (USD) and intraoperative ultrasonography (IOUS) have shown encouraging results in a retrospective analysis of 109 patients with benign or malignant liver disease. Of 109 patients assessed between 1980 and 1993, 84 were resected: 27 by finger fracture technique (FFT) and 57 by USD. Hospital mortality was 4.8% (4/84) and 30-day mortality was 6.0% (5/84). Overall morbidity was 48.8% (41/84) and liver related morbidity (hepatic bleeding, sepsis, and bile leak) was 34.5% (29/84); of the 29 patients, 5 required re-operation. Liver complications occurred in 12/27 (44.4%) in the FFT group as opposed to 17/57 (29.8%) in the USD group. The incidence of postoperative hepatic bleeding was significantly less by USD than by FFT( p =O.03). As well, intraoperative blood loss ( p =O.01)number of intraoperative blood units used ( p =0.002), and postoperative length of stay ( p =O.O09) have been significantly reduced by USD. IOUS was used on 64 patients. Not only has it improved the sensitivity (99%) and specificity (98%) for detection of hepatic neoplasms, it has also helped increase the precision and accuracy of anatomical tumour localization. As a result, 11/64 patients (17.2%) had their preoperative plans changed: 8 were abandoned and 3 were revised. In summary, USD has significantly reduced intraoperative blood loss and hence reduced the number of intraoperative transfusions, incidence of postoperative complications and postoperative length of stay. IOUS should be routinely employed in patients undergoing liver resection since it provides critical information that could obviate oncologically useless resections.